Dampak Pola Asuh Otoriter Terhadap Kesejahteraan Psikologis: Studi Kasus Pada Siswa Sekolah Menengah Atas - Dari, Wulan; Hendar, Kus; Ariyati, Ika (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2025)
Authoritarian parenting is an important focus in child developmental psychology considering that authoritarian parenting has a very significant impact on psychological well-being. The main characteristic of authoritarian parenting is extreme control over children's needs so that it can hinder children's emotional, social, and independent development). This study aims to analyze the influence of authoritarian parenting on the psychological well-being of students at SMA Taruna Gajah Mada Metro. This study uses a quantitative method with a simple linear regression analysis on 155 students selected through simple random sampling. Data collection was carried out using two scales, namely the PAQ scale with validity (ps<.001) = 0.94 and reliability (α = 0.77-0.92) and the PWB scale with validity (V=0.6-0.95) and reality (α=0.543-0.828). The results of the analysis showed that two classical assumption tests, namely the normality and linearity tests, were met, with a significance value of >0.05. The results of the simple linear regression test also show that authoritarian parenting has a significant influence on the psychological well-being of students. This can be seen from the significance value of less than 0.05, which is 0.000. The simple linear regression equation obtained is Y = 38.284 + 0.166X with the result of the R Square value of 0.13. So it can be concluded that authoritarian parenting has a significant influence, which is 13% on the psychological well-being of students at SMA Taruna Gajah Mada Metro.